2021
DOI: 10.1088/1742-6596/1793/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis for the Influence of Ignition Time on Combustion Characteristics of a Free Piston Engine Linear Generator

Abstract: Free Piston Engine Linear Generator (FPELG) is a modern engine and promising power generation engine. It has many advantages compared to conventional engines such as less friction, few numbers of parts, and high thermal efficiency. The cycle-to-cycle variation one of the big challenges of the FPELG because it is influence on the stability and output power of the engine. Therefore, in this study, the effect of ignition time on combustion characteristics is investigated. The single-cylinder FPELG with spark igni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Thus, this type of FPELG requires controlling some parameters, and a highly accurate control strategy requires too 6,7,15) . The researchers in previous studies focused on some parameters such as ignition timing and piston motion control of FPELG 12,16,17,18,19) . The forces generated by FPELG were classified into the forces that come from in-cylinder pressure for each side of FPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this type of FPELG requires controlling some parameters, and a highly accurate control strategy requires too 6,7,15) . The researchers in previous studies focused on some parameters such as ignition timing and piston motion control of FPELG 12,16,17,18,19) . The forces generated by FPELG were classified into the forces that come from in-cylinder pressure for each side of FPE.…”
Section: Introductionmentioning
confidence: 99%
“…However, the piston motion of FPELG has different characteristics compared to the conventional engine. Because there is no crankshaft for FPELG the differences can be described by the association between the engine performance and the injection position, ignition timing, and injection timing 19) . Moreover, the crank angle value in conventional engines was used as an injection timing signal value.…”
Section: Introductionmentioning
confidence: 99%
“…10 Raheem et al studied parameters affecting FPEG performance through experiments, and the results showed that piston motion control is the key issue to affect FPEG stability. 11 ZHANG et al studied the influence of structural parameters on generator performance by simulation, and the results showed that cylinder diameter ratio and stroke have great influences on thermal efficiency, fuel economy and ignition position. 12 Feng et al studied the influence of key parameters on the startup process, proposed a method for comprehensive optimization of design and operation parameters, and investigated the impact of key design parameters (like the mover assembly mass and stroke ratio) on the system operation characteristics.…”
Section: Introductionmentioning
confidence: 99%